2009
DOI: 10.1007/s10552-008-9289-4
|View full text |Cite
|
Sign up to set email alerts
|

Previous pulmonary disease and family cancer history increase the risk of lung cancer among Hong Kong women

Abstract: Chinese women in Hong Kong have among the highest incidence and mortality of lung cancer in the world, in spite of a low prevalence of smoking. We carried out this population-based case-control study to evaluate the associations of previous lung disease and family cancer history with the occurrence of lung cancer among them. We selected 212 cases that were newly diagnosed with primary lung cancer, and randomly sampled 292 controls from the community, frequency matched by age group. All the cases and controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…In our previous analyses [10,11], we found that smoking and exposure to cooking emission were potent risk factors for lung cancer in the Hong Kong women, in which the two factors appeared to act independently. We also observed that a positive family history of any cancer was associated with over twofold risk of a negative family history [12]. The present analysis reconfirmed the associations, while additional factors, such as dietary habits, occupations, and exposure to radon at home were adjusted simultaneously.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our previous analyses [10,11], we found that smoking and exposure to cooking emission were potent risk factors for lung cancer in the Hong Kong women, in which the two factors appeared to act independently. We also observed that a positive family history of any cancer was associated with over twofold risk of a negative family history [12]. The present analysis reconfirmed the associations, while additional factors, such as dietary habits, occupations, and exposure to radon at home were adjusted simultaneously.…”
Section: Discussionsupporting
confidence: 79%
“…In our previous data analysis using the same database, we evaluated the effects of exposure to cooking emissions and smoking on lung cancer [10,11], both of which were found to be potent risk factors in these women. In another recent report [12], we determined the associations of previous lung diseases and family cancer history with the occurrence of lung cancer. In the present analysis, we attempt to provide an overall picture of risk factors in the population using integrated data covering a wide range of variables including occupations and detailed dietary factors, which has been rarely done in addressing etiological issues of lung cancer in Hong Kong population.…”
Section: Introductionmentioning
confidence: 99%
“…However, in East Asia, smoking is much less prevalent in women than men by 5% versus 50% in general population and by 11% versus 80% in lung cancer patients (Ando et al, 2003;Liaw et al, 2005;Thun et al, 2008;Scagliotti et al, 2009). Risk factors for lung cancer in Asian never-smokers include previous pulmonary diseases, family cancer history, environmental tobacco smoke, cooking fumes exposure, ingested arsenic and human papillomavirus infection (Chen et al, 2004a, b;Yu et al, 2006;Tse et al, 2009;Wang et al, 2009b). Furthermore, the abnormal molecular signatures in lung cancer tissue are very different when smokers and non-smokers are compared (Carolan et al, 2008;Tan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Chronic infl ammation results in a high cell turnover rate with a higher possibility of spontaneous mutation; it can reduce the clearance of inhaled toxins and carcinogens that are found in the bronchoalveolar epithelium [8] or it can cause greater susceptibility to oxidant-induced alterations [22]. Also, antioxidant levels in the respiratory tract of patients with asthma are low [23]; free radical-induced cell ageing and oxidants cause direct damage to DNA, which can contribute to lung carcinogenesis [11,20]. (3) IL-6 plays a key role in the host defence mechanisms; it is the main cytokine detected in lung tumour tissue [24], and can be found at high levels in epithelial cells and peripheral blood of asthma patients [25].…”
mentioning
confidence: 99%
“…The incorrect asthma classifi cation could explain the lung cancer risk increase observed. The defi nition of asthma used in some studies seems to have included patients affected by other lung, smoking-related conditions, especially chronic bronchitis and emphysema [30], since they can have similar medical manifestations; early lung cancer symptoms could also have been misclassifi ed as asthma [11,30], hence unrealistically increasing the extent of the association. However, the risk increase did not change [8] in several case studies and controls which excluded the cases with an asthma diagnosis up to 5 years prior to the cancer diagnosis.…”
mentioning
confidence: 99%